Lonicera caerulea Berry Polyphenols Extract Alleviates Exercise Fatigue in Mice by Reducing Oxidative Stress, Inflammation, Skeletal Muscle Cell Apoptosis, and by Increasing Cell Proliferation - Liu, Suwen; Meng, Fanna; Zhang, Dong; Shi, Donglin; Zhou, Junyi; Guo, Shuo; Chang, Xuedong (Frontiers in Nutrition, 2022)
Exercise fatigue can exert deleterious effects on the body. This study evaluated the effects and mechanisms by which Lonicera caerulea berry polyphenols extract (LCBP) improved the treadmill endurance of mice. Comparison was performed between the effects at 25 °C and low temperatures (-5 °C). Energy storage, product metabolism, and other biochemical indices were determined using vitamin C (VC) as a positive control. Co-immunoprecipitation was performed to detect the interaction between different proteins. Dietary supplementation with LCBP significantly prolonged the exhaustion time during treadmill exercise by 20.4% (25 °C) and 27.4% (-5 °C). LCBP significantly regulated the expression of antioxidant and inflammatory proteins, Bcl-2 /Bax apoptosis proteins, and the PKCα -NOx2 / Nox4 pathway proteins, and activated the expression of AMPK-PGC1α -NRF1-TFAM proteins in skeletal muscle mitochondria. The gene and protein expression of miRNA-133a/IGF-1/PI3K/Akt/mTOR in skeletal muscle cells was also activated. Molecular docking confirmed that the main components of LCBP such as cyanidin-3-glucoside, catechin, and chlorogenic acid, have strong binding affinity towards AMPKα. LCBP alleviates exercise fatigue in mice by reducing oxidative stress, inflammation, and apoptosis of skeletal muscle cells, enhances mitochondrial biosynthesis and cell proliferation, reduces fatigue, and enhances performance. These effects are also significant in a low-temperature environment. Consequently, these results provide novel insights into the anti- fatigue roles of LCBP in exercise fatigue.